2020
DOI: 10.3390/soc10020039
|View full text |Cite
|
Sign up to set email alerts
|

Educational Legacy of the Rio 2016 Games: Lessons for Youth Engagement

Abstract: The promise of the Rio 2016 Games was to influence the entire population of Brazil, but the major impact was expected to be on children and the youth. The development of youth education programs promoting Olympic and Paralympic values was one of the main commitments that organizers made in 2009 to host the 2016 Olympic and Paralympic Games. This article draws on the available literature on Olympic and Paralympic education and youth engagement and examines several of such programs previously implemented in such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Widespread evidence of a lack of resources and pedagogical guidance (dos Santos 2018) as well as a disbelief in the sustainable legacy (Rocha 2020) may explain the non-significant variation of teacher's perception post-Games. Previous studies have also identified difficulties in integrating its pedagogic contents into mainstream school education in Brazil due to the governmental changes that occurred in secondary education (Kirakosyan 2020). Another alternative explanation for this finding might be the increase in Brazil's economic and political problems (Rocha 2020), which contributed to halting the Transforma in 2016, and as a result, teachers may have perceived a decrease in network/social exchange in the following post-Olympic years.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Widespread evidence of a lack of resources and pedagogical guidance (dos Santos 2018) as well as a disbelief in the sustainable legacy (Rocha 2020) may explain the non-significant variation of teacher's perception post-Games. Previous studies have also identified difficulties in integrating its pedagogic contents into mainstream school education in Brazil due to the governmental changes that occurred in secondary education (Kirakosyan 2020). Another alternative explanation for this finding might be the increase in Brazil's economic and political problems (Rocha 2020), which contributed to halting the Transforma in 2016, and as a result, teachers may have perceived a decrease in network/social exchange in the following post-Olympic years.…”
Section: Discussionmentioning
confidence: 99%
“…However, this finding needs to be discussed beyond the results obtained. Different from the Vancouver 2010 and London 2012 education programs that continued after the Games with local stakeholder support (Kirakosyan 2020), Transforma ended in 2016 without prospects for future continuity (Rocha 2020). Thus, the first explanation for this finding is that the Impulsiona program appears focused on encouraging the use of sports as an educational tool in Brazilian schools (Impulsiona 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, these educational interventions should disseminate an Olympic values-based curriculum and ideals to shape the younger character into their adulthood (Teetzel, 2012). Third, they should promote leadership, engagement, and social inclusion through innovative approaches that foster social behaviour change (Kirakosyan, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%